Experiential Learning in Managing CBPA Community Extension Cooperatives: Students’ Skills and Community Benefits - Domingo, Michael Darwin; Aurin, Charmee Grace; Valencia, Darylle; Pamintuan, Jennel Sophia; Cano, Kevin Hard; Peñalosa, Ma. Carmela; Osias, Mariel Heart (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined experiential learning in managing CBPA Community Extension Cooperatives and its relationship with students’ skills development and community benefits. Anchored on experiential learning as active participation, reflection, and application in real-world contexts, the study assessed experiential learning in terms of economic and business support, educational outreach, social development, and relevance to academic and marketing programs. A descriptive research design was used, with data gathered through a researcher-made structured survey questionnaire administered via Google Forms. The respondents were fifty (50) purposively selected participants composed of thirty (30) CBPA students, ten (10) community cooperative members, and ten (10) faculty members and program coordinators. Data were analyzed using frequency, percentage, weighted mean, Pearson Product-Moment Correlation Coefficient, and p-value. Findings showed that experiential learning was highly evident, with an overall weighted mean of 4.21; students’ skills were highly developed, with an overall weighted mean of 4.42; and community benefits were highly evident, with an overall weighted mean of 4.53. A significant strong positive relationship was found between experiential learning and students’ skills (r = 0.6455, p = 0.0001), while no significant relationship was found between experiential learning and community benefits (r = 0.3575, p = 0.0524). The study concludes that experiential learning significantly enhances students’ communication, critical thinking, leadership, entrepreneurial, and financial management competencies, while community benefits may also depend on institutional support, stakeholder participation, resources, and program sustainability. The study recommends strengthening experiential learning activities, training and mentoring programs, sustainability plans, partnerships, and continuous monitoring and evaluation. The study supports SDG 4, SDG 8, SDG 11, and SDG 17 by promoting competency-based education, cooperative economic participation, sustainable communities, and institutional partnerships. Its sustainability impact lies in strengthening educational practice, community development, cooperative operations, and long-term institutional engagement.